LEGAL STATUS OF ENSURING EFFICIENCY OF LAND USE OF FARMS IN UZBEKISTAN - Tukhtashev Khikmatilla Ismatillayevich (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, national and foreign laws related to increasing the efficiency of agricultural land use by farms, the issue of using modern technologies in land use are analyzed from a scientific theoretical point of view. Also, along with the national legal documents regulating the activities of agricultural entities, normative documents aimed at the legal regulation of agricultural land were studied. The specific experiences of foreign countries on the use of agricultural irrigated land, dry land and pasture land of farms were analyzed based on the comparative research method. Consequently, opinions and considerations were given regarding the use of effective aspects of drip irrigation in agriculture in the dry and moderate climate of Uzbekistan and the creation of its legal basis. Ways to improve the procedure for providing subsidies to farms and the legal basis for applying incentives to increase the efficiency of land use were considered. Attempts were made to make suggestions and recommendations on the improvement of national legislation using the best experiences of foreign countries.